An examination of the cytomorphological trends in tuberculous lymphadenitis at a tertiary care hospital of southern Assam - Sukanya Choudhury; Payel Hazari; Nicky Choudhury; Shah Alam Sheikh (Journal of Current Oncology and Medical Sciences)
Introduction: Tuberculous lymphadenitis is a leading cause of lymph node enlargement accounting for 195 per 1,00,000 population in India. Fine needle aspiration cytology (FNAC) is rapid and economical compared to other tests and thus plays a crucial role in diagnosing this condition. It prevents unnecessary biopsy of lymph nodes and it can be used for collection of material for cytomorphological and bacteriological examination. This study aimed to assess the cytomorphological patterns of tuberculous lymphadenitis and correlate them with Ziehl-Neelsen (ZN) staining.